Improvement of the Mo/TiO2-Al2O3 catalyst by the control of the sol-gel synthesis - Cecilio, A. A.; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP]; Maniette, Y.; Da Silva, V. T. (Kluwer Academic Publ, 2004)
Traditional hydrotreating catalysts are constituted by molybdenum deposited on Al2O3 promoted by nickel and phosphorous. Several studies have shown that TiO2-Al2O3 mixed oxides are excellent supports for the active phases. Results concerning the preparation, characterization and testing of molybdenum catalyst supported on titania-alumina are presented. The support was prepared by sol-gel route using titanium and aluminum isopropoxides, the titanium one chelated with acetylacetone (acac) to promote similar hydrolysis ratio for both the alcoxides. The effect of nominal molar ratio [Ti]/[Ti+Al] on the microstructural features of nanometric particles was analyzed by X-Ray Diffraction, N-2 Adsorption Isotherms and Transmission Electron Microscopy. The catalytic activity of Mo impregnated supports was evaluated using the thiophene hydrodesulfurization at different temperatures and atmospheric pressure. The pores size distribution curve moves from the micropores to the mesopores by increasing the Ti contents, allowing the fine tuning of average size from 2.5 to 6 nm. Maximal (367 m(2).g(-1)) and minimal (127 m(2).g(-1)) surface area were found for support containing [Ti]/[Ti+Al] ratio equal to 0.1 and 1, respectively. The good mesopore texture of alumina-titania support with [Ti]/[Ti+Al] molar ratio between 0.3 and 0.5 was found particularly valuable for the preparation of well dispersed MoS2 active phase, leading to HDS catalyst with somewhat higher activity than that prepared using a commercial alumina support.
Keywords: porous texture; alumina-titania catalysts; hydrodesulfurization; TEM